Pengaruh Penggunaan Lembar Kerja Siswa (Lks) Berbasis Model Problem Solving Polya Pada Konsep Fluida Dinamis Terhadap Kemampuan Menganalisis Siswa - Hidayat, Tofik (Jurnal Gemaedu, 2018)
This study aims to determine the effect of LKS based on Polya problem-solving model on the concept of dynamic fluid on the students' ability to analyze. This research was conducted in class XI IPA 1 and XI IPA 4 SMA Negeri 7 Kota Tangerang Selatan. This research took place in April 2014. The research method used was quasi-experiment with nonequivalent control group design and sampling technique with purposive sampling. The instrument used is a test instrument in the form of questions and notes instrument in the form of activity observation sheet and student response questionnaire. Based on the analysis of test data, obtained the result that there is the influence of LKS based on Polya problem-solving model on the concept of dynamic fluid to the students' ability to analyze. It is based on the hypothesis test result by using t-test. The result  t-count = 5.31 while table = = 2.00. It can be seen that tcount> table, so H0 is rejected. In addition, learning using LKS-based problem-solving Polya proved superior in improving students' analytical skills. Based on the results of the N-Gain test the ability to analyze on differentiating aspects increased by 0.46 (medium), organized increased by 0.57 (medium), and attributed increased by 0.44 (medium) or an average increase of 0.52 ( medium). Furthermore, based on notes data analysis in the form of student activity observation sheet, the application of LKS based solving problem Polya is in a good category with a percentage of 72%. The result of student's questionnaire analysis also shows that LKS based on Polya problem solving is in the good category with percentage 69,33%